Order of Play: Disorder of the World - Esposito, Elena (Into the Magic Circle: Rethinking Homo Ludens, 2024)
In the course of society’s evolution the way the distinction between playful and serious relates to other social distinctions has changed considerably, affecting the scope and significance of play as such. This paper analyses the relevance of play in modern society on the basis of its independence from other fields of life. Play’s loss of relevance in modern society, we argue, is the condition to carry out its specific function – confirming and contradicting Huizinga’s thesis about its marginalization.